Prescribing Pattern of Antifungal Medications at a Tertiary Care Hospital in Oman - Al Balushi, Khalid A. (J Clin Diagn Res, 2016)
INTRODUCTION: Inappropriate use of antifungal agents is implicated in the global burden of antifungal resistance, adverse outcomes like persistent infections, unnecessary exposure and increased cost. Data collection from time to time is to be done in order to have a check on the resistance/sensitivity pattern of the commonly prescribed antifungal drugs. AIM: To describe the pattern of antifungal drug prescription and administration to patients attending a university hospital in Oman. MATERIALS AND METHODS: This was a descriptive, retrospective cross-sectional study conducted at Sultan Qaboos University Hospital (SQUH), a university hospital in Oman that covered the electronic patient’s data for a period of one year (January 2013 to December 2013). The study included inpatients and outpatients of all ages and both genders attending SQUH and receiving antifungal medications at the study period. Frequencies and percentages were reported for categorical variables, while the mean and standard deviation were used to summarize the data for continuous variables. RESULTS: A total of 1353 antifungal drug prescriptions were prescribed for 244 patients. More than half of all antifungal drug prescriptions were prescribed by haematology, infectious disease and family medicine departments. The majority of patients to whom these drugs were prescribed were diagnosed to have infectious diseases followed by prophylactic use in leukaemias and immunocompromised conditions. Fluconazole was the most commonly prescribed antifungal drug (n=715, 52.8%) followed by nystatin and voriconazole (n=233; 17.2% and n=152; 11.2%, respectively). CONCLUSION: This study will help in understanding antifungal prescription practices and help in directing future studies and also in developing local policies for appropriate use of antifungal drugs.